(untitled) (Bangladesh Journal of Medical Science, 2022)
Background: In Saudi Arabia, due to its dynamic population and annual hajj pilgrimage, there is influx and efflux of millions of visitors every year, especially to Makkah dan Madinah, providing an international hub for the exchange of microbes. It is rather a common interest to understand the molecular epidemiology and clinical significance of multidrug resistant organisms in this country. Acinetobacter baumannii in particular, is one of the most common Gram negative bacteria isolated in the Kingdom. This organism is responsible for ventilator associated pneumonia, blood stream infections, urinary tract infections and skin infections. Objective: In this manuscript we aim to review the literature available on the antimicrobial resistance, genotypes and clinical significance ofA. baumannii acquisitions in Saudi Arabia. Methodology: The literature was reviewed systematically using PubMed with a combination of the terms ‘Acinetobacter’ AND ‘Saudi Arabia’. Reference lists of relevant articles were searched to identify further material. We only included studies with plausible data. Main observations: In Makkah itself, there are significant increase in carbapenem resistant Acinetobacter from 14% in 2004-2005, 46% in 2005-2006, 63% in 2011 to 90% in 2015. Recent publication from Madinah indicated, beside resistant to carbapenem approaching 90%, an alarming resistant rate to the last resort antibiotic, polymyxin is also observed at 24% of 379 tested strains. In a study in Makkah, the most predominant sequence types being ST 195 and ST557, which in the worldwide clonal complex 2. Conclusion: These resistant rate and sequences type indicated intermingling of the resistant superbugs occurred. With limited treatment option, effective infective control measures and antibiotic stewardship programs are the key element to contain these resistant isolates from spread. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 233-242